Transcriptome-Based Study on the Phylogeny and Hybridization of Marattialean Ferns (Marattiaceae) - Jing Zhao; Xinmao Zhou; Shaoli Fang; Zhangming Zhu; Yuxin Li; Hong Yu; Zhaorong He (Plants, 2023)
Marattiaceae is a phylogenetically isolated family of tropical eusporangiate ferns including six genera with more than one-hundred species. In Marattiaceae, monophyly of genera has been well-supported phylogenetically. However, the phylogenetic relationships among them were elusive and controversial. Here, a dataset of 26 transcriptomes (including 11 newly generated) were used to assess single-copy nuclear genes and to obtain the organelle gene sequences. Through phylotranscriptomic analysis, the phylogeny and hybridization events of Marattiaceae were explored and a robust phylogenomic framework for the evolution of Marattiaceae was provided. Using both concatenation- and coalescent-based phylogenies, the gene-tree discordance, incomplete lineage sorting (ILS) simulations, and network inference were examined. Except the low support with mitochondrial genes of Marattiaceae, nuclear genes and chloroplast genes strongly supported a sister relationship between Marattiaceae and leptosporangiate ferns. At the genus level, all phylogenetic analysis based on nuclear genes datasets recovered five genera in Marattiaceae as monophyletic with strong support. Danaea and Ptisana were the first two diverged clades in turn. Christensenia was a sister clade to the clade Marattia + Angiopteris s.l. In Angiopteris s.l., three clades (Angiopteris s.s., the Archangiopteris group, and An. sparsisora) were well identified with maximum support. The Archangiopteris group was derived from Angiopteris s.s. at ca. 18 Ma. The putative hybrid species An. sparsisora between Angiopteris s.s. and the Archangiopteris group was verified by the species network analyses and the maternal plastid genes. This study will improve our understanding for using the phylotranscriptomic method to explore phylogeny and investigate hybridization events for difficult taxa in ferns.